Judicial permissibility in a marriage lacking legal capacity and its impact on increasing divorce cases - Ali Abdul Azeez AlGburi (Journal of Madenat Alelem University College, 2024)
With increasing calls to limit the marriage of minors through the media and seminars held by civil society organizations defending women and demanding their rights, and claims of an increase in divorce rates in particular for this group. This study came to determine the extent of the impact of judicial permissibility based on the text of Article (8) of the Personal Status Law No. 188 of 1959, as it explained the meaning of eligibility, its levels, conditions for achieving it, and everything related to the marriage of a minor from a legal perspective. It then shed light on the rates of marriage of minors compared to adults and the rates of divorce in these two categories through a field study in both the Personal Status Courts in Al-Kadhimiya and Dhat Al-Silsil and reviewing related records, and concluded with a set of results and recommendations.